Studi Numerik Pengaruh Variasi Rasio Diameter Silinder Pengganggu di Depan Returning Blade Terhadap Coefficient of Power (CP) Turbin Angin Savonius Penambahan Fin - Ryandika Aditya Pramanta; Priyo Agus Setiawan; Nopem Ariwiyono (Politeknik Perkapalan Negeri Surabaya, 2023)
Experimental research on savonius wind turbine with additional fins and variouscircular cylinders have been carried out as an effort to improve the turbine performance.Further research is needed to validate experimental studies.Based on the problems above,numerical studies using 3-dimensional Computational Fluid Dynamics (CFD) method isneeded to determine coefficient of torque values. The turbine has the same diameter and heightof 0.4 meters with additional fins. The various diameter of circular cylinder used are ds/D =0.1; ds/D = 0.2; ds/D = 0.3; and ds/D = 0.4. Then the cylinder is placed at a distance of X =34 cm and Y = 10 cm. The final result is the turbine can reach the highest increase of 5.4% inits performance with ds/D = 0.4 with 0.389 coefficient of power (Cp).